A proof-of-concept study exploring the effects of impulsivity on a gamified version of the stop-signal task in children - Gallagher, Ruth; Kessler, Klaus; Bramham, Jessica; Dechant, Martin; Friehs, Maximilian A. (Frontiers in Psychology, 2023)
This proof-of-concept study provides an appraisal of a remotely administered gamified Stop-Signal Task (gSST) in a child sample. Performance on the task has been shown previously to differentiate attention-deficit-hyperactivity-disorder groups from controls. The advantage of the gSST is that it is less monotonous and has the potential to provide higher data quality in child samples. The gSST was administered remotely via video chat to 30 child participants within a community sample aged 8-12 to investigate the effect of ADHD symptoms and intrinsic motivation on gSST performance. Qualitative data was collected based on feedback from participants to gain insight into how the gSST was received by participants. A positive correlation was observed between impulsive/hyperactivity and gSST performance, however there was insufficient evidence to suggest that impulsivity predicted performance. With regards to accuracy, results suggested that impulsivity level significantly predicted the rate of go-omission errors. No relationships were observed between intrinsic motivation inventory (IMI) subscales and performance or IMI and impulsivity. Nevertheless, mean IMI scores were overarchingly high for each of the IMI subscales, suggesting that regardless of performance and/or level of impulsive behaviour, the child sample obtained in this study demonstrated high levels of intrinsic motivation, which was supported by the predominantly positive subjective feedback provided by the child participants. The present study provides some evidence based on quantitative and qualitative results for the efficacy of gSST for use with children.